Testing Homogeneity of Time-Continuous Rating Transitions - Claudia Lawrenz; Patrick Tschiersch; Rafael Weißbach (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
Banks could achieve substantial improvements of their portfolio credit risk assessment by estimating rating transition matrices within a time-continuous Markov model, thereby using continuous-time rating transitions provided by internal rating systems instead of discrete-time rating information. A non-parametric test for the hypothesis of time-homogeneity is developed. The alternative hypothesis is multiple structural change of transition intensities, i.e. time-varying transition probabilities. The partial-likelihood ratio for the multivariate counting process of rating transitions is shown to be asymptotically c2 -distributed. A Monte Carlo simulation finds both size and power to be adequate for our example. We analyze transitions in credit-ratings in a rating system with 8 rating states and 2743 transitions for 3699 obligors observed over seven years. The test rejects the homogeneity hypothesis at all conventional levels of significance.
Keywords: G33; G18; G11; C51; 519; Portfolio credit risk; Rating transitions; Markov model; time-homogeneity; partial likelihood; Kreditwürdigkeit; Matrizenrechnung; Zeitökonomik; Statistischer Test; Theorie; Deutschland